Infographic Design as Visualization of Geography Learning Media. (April 2018) - Akhmad, R; Sugandi, D; Nandi, N; Rahmawati
Abstract: Infographics is an integration visualization technique that combines text with images into an illustration. Info graphic designs were used to convey a complex message or material, into an interesting visual data. Geography as a subject that plays a role in introducing natural phenomena, it is considered very important to choose the right media in visualizing the material well. So this research literature study done with purpose can introduce info graphic design to educational world, as visualization of interesting media of learning. Especially for schools that have a diversity learner in certain classes. With the media-based design of this info graphic will facilitate teachers in teaching and motivating students in learning.